Barriers and facilitators influencing death at home: A meta-ethnography. (February 2018) - Wahid, Abdul Samad; Sayma, Meelad; Jamshaid, Shiraz; Kerwat, Doa'a; Oyewole, Folashade; Saleh, Dina; Ahmed, Aaniya; Cox, Benita; Perry, Claire; Payne, Sheila
Background: In many countries, achieving a home death represents a successful outcome from both a patient welfare and commissioning viewpoint. Significant variation exists in the proportion of home deaths achieved internationally, with many countries unable to meet the wishes of a large number of patients. This review builds on previous literature investigating factors influencing home death, synthesising qualitative research to supplement evidence that quantitative research in this field may have been unable to reach. Aim: To identify and understand the barriers and facilitators influencing death at home. Design: Meta-ethnography. Data sources: The review adhered to the PRISMA guidelines. A systematic literature search was conducted using five databases: PubMed, EMBASE, Ovid, CINAHL and PsycINFO. Databases were searched from 2006 to 2016. Empirical, UK-based qualitative studies were included for analysis. Results: A total of 38 articles were included for analysis. Seven overarching barriers were identified: lack of knowledge, skills and support among informal carers and healthcare professionals; informal carer and family burden; recognising death; inadequacy of processes such as advance care planning and discharge; as well as inherent patient difficulties, either due to the condition or social circumstances. Four overarching facilitators were observed: support for patients and healthcare professionals, skilled staff, coordination and effective communication. Conclusion: Future policies and clinical practice should develop measures to empower informal carers as well as emphasise earlier commencement of advance care planning. Best practice discharge should be recommended in addition to addressing remaining inequity to enable non-cancer patients greater access to palliative care services.